2008
DOI: 10.2215/cjn.03330807
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin Is Strongly Associated with Erythropoietin Sensitivity in Hemodialysis Patients

Abstract: Background and objectives: In hemodialysis patients, the hematological response to erythropoietin (epo) is variable and clinical factors that explain this variability are incompletely understood. We tested the hypothesis that the variability in hemoglobin (Hgb) response (epo sensitivity) is determined by key nutritional, inflammation, and oxidative stress markers.Design, setting, participants, & measurements: Eighty-two consecutive patients on hemodialysis had 3 consecutive monthly predialysis evaluations of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 28 publications
(24 reference statements)
4
41
1
Order By: Relevance
“…Serum Ferr and TSat have been used as the two primary markers of iron available for erythropoiesis. However, many studies have failed to show the effect that these markers have on the erythropoietic response (7,16,(25)(26)(27). Our analysis indicates that both markers are associated with the moderation of the erythropoietic response.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Serum Ferr and TSat have been used as the two primary markers of iron available for erythropoiesis. However, many studies have failed to show the effect that these markers have on the erythropoietic response (7,16,(25)(26)(27). Our analysis indicates that both markers are associated with the moderation of the erythropoietic response.…”
Section: Discussionmentioning
confidence: 61%
“…Among these factors, iron stores are most thoroughly described (7)(8)(9)(10)(11). Other factors include inflammation (12,13), adequacy of dialysis (14,15), nutritional status (16), and hyperparathyroidism (17).…”
mentioning
confidence: 99%
“…Therefore, albumin level could be considered a marker of nutritional status as well as inflammation. Malnutrition and inflammation can cause hypoalbuminemia and also suppress erythropoeisis since the elevated levels of cytokines particularly IL-1, mediates acute phase response, enhances CRP production and reduces albumin level and transferrin synthesis [19]. Low level of transferrin prevents transportation of iron to the hematopoietic sites and leads to suppression of Hgb synthesis as well as hyporesponsiveness to ESA [41].…”
Section: Individual Response Variations To Erythropoietin Stimulatingmentioning
confidence: 99%
“…Main factors associated with ESA resistance include iron deficiency [18] low serum albumin level [19], malnutrition [20], hyperparathyroidism [21], suboptimal dialysis [22]; however, ESA resistance is still an incompletely understood problem. Therefore, identifying the factors that associate with ESA resistance is important not only in reducing the costs associated with the treatment, but also possibly in influencing patients' mortality risks.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ESA hyporesponse is dynamic and must be evaluated on an ongoing basis. One study found that an acute-phase reactant, serum albumin concentration, tracks closely with ESA response (24). Larger studies are needed to determine whether serum albumin and change in serum albumin can be used to track ESA responsiveness and individualize therapy.…”
Section: Defining Hyporesponsementioning
confidence: 99%